2013
DOI: 10.1136/gutjnl-2013-306219
|View full text |Cite
|
Sign up to set email alerts
|

mAb Das-1 is specific for high-risk and malignant intraductal papillary mucinous neoplasm (IPMN)

Abstract: Objective Intraductal papillary mucinous neoplasm (IPMN) consists of four epithelial subtypes that correlate with histological grades and risks for malignant transformation. mAb Das-1 is a monoclonal antibody against a colonic epithelial phenotype that is reactive to premalignant conditions of the upper GI tract. We sought to assess the ability of mAb Das-1 to identify IPMN with high risk of malignant transformation. Design mAb Das-1 reactivity was evaluated in 94 patients with IPMNs by immunohistochemistry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…Both the EUS-FNA cyst fluid analysis (specificity and sensitivity of 100% and 89%, respectively) and histological specimens from resected high-grade IPMNs (specificity and sensitivity of 95% and 85%, respectively) showed that Das-1 has potent reactivity (69).…”
Section: Current Practice and The Updates On The Genomic Fieldmentioning
confidence: 99%
“…Both the EUS-FNA cyst fluid analysis (specificity and sensitivity of 100% and 89%, respectively) and histological specimens from resected high-grade IPMNs (specificity and sensitivity of 95% and 85%, respectively) showed that Das-1 has potent reactivity (69).…”
Section: Current Practice and The Updates On The Genomic Fieldmentioning
confidence: 99%
“…In a collaborative effort with the Rutgers Robert Wood Johnson Medical School, we have also found that mAb Das-1, a monoclonal antibody that reacts specifically with normal colonic epithelium and intestinal metaplasia of the lower esophagus (Barrett's esophagus), can identify high-risk IPMN using cyst fluid with a sensitivity and specificity of 89 and 100%, respectively [55]. A preliminary, multi-institutional validation study of the performance of mAb Das-1 confirmed our initial findings and suggests that this antibody may be a valuable addition to current clinical guidelines [56].…”
Section: Cyst Fluid Analysis: Proteins Cytology and Molecular Charamentioning
confidence: 99%
“…One other promising marker for identifying IPMNs which require surgical resection is mAb Das-1, a monoclonal antibody which is found in premalignant conditions of the gastrointestinal tract. In preliminary studies, it had 85% sensitivity and 95% specificity for identifying IPMNs with high-grade dysplasia or invasive cancer and is now being evaluated in a multicenter study [33]. …”
Section: Intraductal Papillary Mucinous Neoplasms and Mucinous Cysticmentioning
confidence: 99%